Introduction [in Boosting growth to end hunger by 2025: The role of social protection] - Wouterse, Fleur Stephanie; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2018)
The 2017–2018 Annual Trends and Outlook Report (ATOR) takes an in-depth look at social protection in rural Africa. First, it summarizes the available evidence on successful implementation of social protection programs in rural Africa. Second, the report helps to fill knowledge gaps related to enhancing the role of social protection in reducing vulnerability and increasing resilience of rural households as Africa embarks on the implementation of the Malabo Declaration commitments and the African Union’s Agenda 2063. Third, the report highlights policy implications to guide the design and roll-out of national social protection programs for rural Africa.